Risk factors for oral allergy syndrome in patients with seasonal allergic rhinitis - Caliskaner, Zafer; Naiboglu, Baris; Kutlu, Ali; Kartal, Ozgur; Ozturk, Sami; Onem, Yalcin; Sener, Osman (Medicina Oral S L, 2011)
Background: Oral allergy syndrome (OAS) is a unique allergic reaction to food, which is caused by cross-reactivity between proteins in fresh fruits or vegetables and pollens. Predisposing factors for OAS are not well known in patients with seasonal allergic rhinitis. Objective: Identify the probable risk factors for OAS in patients with seasonal allergic rhinitis. Study Design: One hundred and eleven consecutive patients with seasonal allergic rhinitis were included. Patients were evaluated in terms of symptom scores and skin prick test positivity scores. Prick-by-prick tests with the fresh fruit or vegetable were carried out in patients who describe oral allergy syndrome. Patients with OAS and without OAS were compared statistically. Results: OAS was more frequent in females than males (p=0.01). Odds ratio for gender (male/female) was 3.80 (95% confidence interval: 1.28-11.32). Within nasal symptoms, only nasal itching was related with OAS (P<0.05). The logistic regression analysis revealed a significant association between the prevalence of the OAS and age, asthma, TSS and TSTP (p<0.05). Conclusion: Not all patients with seasonal allergic rhinitis develop OAS. It is likely that, patients with OAS have some additional risk factors other than atopy.
Keywords: Oral allergy syndrome; anaphylaxis; seasonal allergic rhinitis